Amorphous Hole‐Transporting Material based on 2, 2′‐Bis‐substituted 1, 1′‐Biphenyl Scaffold for Application in Perovskite Solar Cells. Issue 9 (31st March 2017) - Magomedov, Artiom; Sakai, Nobuya; Kamarauskas, Egidijus; Jokubauskaitė, Gabrielė; Franckevičius, Marius; Jankauskas, Vygintas; Snaith, Henry J.; Getautis, Vytautas
Abstract: Perovskite solar cells are considered a promising technology for solar‐energy conversion, with power conversion efficiencies currently exceeding 20 %. In most of the reported devices, Spiro‐OMeTAD is used for positive‐charge extraction and transport layer. Although a number of alternative hole‐transporting materials with different aromatic or heteroaromatic fragments have already been synthesized, a cheap and well‐performing hole‐transporting material is still in high demand. In this work, a two‐step synthesis of a carbazole‐based hole‐transporting material is presented. Synthesized compounds exhibited amorphous nature, good solubility and thermal stability. The perovskite solar cells employing the newly synthesized material generated a power conversion efficiency of 16.5 % which is slightly lower than that obtained with Spiro‐OMeTAD (17.5 %). The low‐cost synthesis and high performance makes our hole‐transport material promising for applications in perovskite‐based optoelectronic devices. Abstract : How to fly a (perovs)kite : Perovskite solar cells are usually considered a promising technology that could expand the uses of solar energy. In most of the reported devices, Spiro‐OMeTAD is used for positive‐charge transport. In this work, carbazole‐basedV997, a hole‐transporting material that can be obtained by a simple two‐step synthetic procedure, is presented. It showed slightly lower performance than Spiro‐OMeTAD, it does not form a crystalline state, and has lower material cost.